Reavaliando o Niilismo em Nietzsche: do problema do vazio à nova luz da perspectiva do eterno retorno - Kaizer, Vitor Leandro (Universidade do Vale do Rio dos Sinos, 2024)
The present doctoral thesis is an investigation into the problem of nihilism in the philosophy of Friedrich Wilhelm Nietzsche (1844–1900). The aim was to reevaluate the situation of nihilism in Nietzsche, seeking a consistent answer capable of solving the main challenges posed by this problem. In this purpose, an initial effort was made to conceptualize nihilism in the clearest possible way, without neglecting its inherent nuances and complexities, thus establishing the sine qua non conditions for overcoming it. Subsequently, the development and critical and reflexive examination of the three main concepts emerging from the experience provided by nihilism were undertaken: the concepts of becoming, will to power and eternal return of the same. It also involved bringing to light the interpretations and proposals for overcoming nihilism that have the most prominence in each of the “lines of thought” raised by such concepts. This, however, was done not only with the intention of verifying the legitimacy of these contributions but, above all, with the aim of establishing references that would make a more complete approach to the problem viable. Next, two theses were examined that seemed to have the conditions to overcome the difficulties encountered so far: that of Luis Enrique de Santiago Guervós and that of Gianni Vattimo. Not having been possible to arrive at a resolution that could account for overcoming certain difficulties of primary importance in the entire problem, an attempt was made to go beyond the alternatives offered there: through an innovative interpretation of the thought of eternal return, a perspective was sought that could provide an efficient answer to what is undoubtedly the supreme challenge imposed by nihilism: the challenge of providing existence with adequate orientation. Grounded in the reflectiveexistential character of the thought that everything returns eternally, the proposal presented has as its main focus to provide orientation capable of addressing the lack of meaning in human existence, but also of endowing it with a satisfactory reason. However, it also proves to be effective in resolving secondary impasses, such as that inherent in the Nietzschean imperative derived from the figure of the Übermensch and that associated with the habitual interpretation of the formula of amor fati.
Keywords: Filosofia; Friedrich Nietzsche; Niilismo; Eterno retorno; Superação; Philosophy; Nihilism; Eternal return; Overcoming; ACCNPQ::Ciências Humanas::Filosofia